GAMBARAN TINGKAT KONSUMSI ENERGI DAN LEMAK SERTA STATUS OBESITAS SENTRAL PADA PEMANDU WISATA - Putu Indri Andaluri Ina Mbitu; Ni Komang Wiardani; Lely Cintari (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2022)
The diet and lifestyle of tour guides tend to follow the lifestyles of tourists who are served which usually tend to be high in energy, fat and cholesterol, making the tour guide vulnerable to obesity and non-communicable diseases. This study aims to determine the level of energy and fat consumption, as well as the status of central obesity in tour guides in Sahadewa Barong and Keris Dance Batubulan. This type of research is observational with a cross-sectional design. The sampling technique uses non-random sampling, namely consecutive sampling technique, carried out in Kabupaten Gianyar with the target of being a tour guide. Data collected included identity, weight, height and waist circumference. The consumption level includes energy and fat consumption using the Recall method 1x24 hours. The data obtained are tabulated, processed and analyzed according to the type and purpose of the study and presented with a frequency distribution table and a cross table. The results showed a sample of 10 people, all male sex. As many 100.0% of the sample experienced central obesity. The results of energy consumption showed that most of the samples had an energy consumption of around 80-110% RDA of 70.0%. As for fat, the majority of consumption is around 80-110% of the RDA of 6 people (60.0%). Samples who have central obesity status with energy consumption 110% RDA totaled 1 person (10.0%), and fat consumption 110% RDA totaled 3 people (30.0%).Keywords: energy and fat consumption level, central obesity status, tour guide